Identity Construction Polemic And Overcoming Radicalism: Case Study Of Hti Transnationalism In Indonesia - Nugraha, Mauludy; Valentine, Easter; Larashati, Fadjria; Ummah, Aniqotul (Universitas Islam Negeri Raden Intan Lampung, 2024)
This research aims to provide an analysis of the activities of the HTI transnationalism movement in Indonesia, especially after the revocation of the Legal Decree. However, behind this incident there is a dilemma for the government, on the other hand there is an obligation to implement freedom of association and ward off the dangers of radicalism. By disbanding HTI, a social identity construction emerged for former HTI members. In this case, they are still active under other names, making the process of monitoring radicalism more difficult. This research uses qualitative methods or literature studies by utilizing previous research and the author's analytical skills in finding facts from the results of other research. In this case, the facts and realities on the ground emerge from research results that the activities of HTI or former HTI members threaten the disintegration of national stability and division due to its vision and goals. Then, after the dissolution, a social identification polemic emerged where there was difficulty in identifying HTI activities. Finally, the role of the central state in this case is to address the issue of the spread of the HTI transnationalist movement in Indonesia, considering that licensing, action, revocation and maintaining the integrity of the Indonesian nation lies in the government's authority which is produced through policy